Production of Microalgae-Derived Exo-Polygalacturonase for Fruit Juice Clarification - Uzuner, Sibel; Uzuner, Sibel; Evrendilek, Gulsun Akdemir; Kurhan, Sebnem (Frontiers Media S.A., 2022)
Due to the growing demand for commercial enzymes derived from renewable and sustainable resources with higher efficacy, algal biomass has gained more attention. Thus, the production of exo-polygalacturonase (PGase) from Bacillus subtilis under submerged fermentation (SmF) using algal feedstocks as a carbon source in fermentation medium and its potential use for the clarification of apple and carrot juices with the optimization of the enzyme loading, pH, and time using Box-Behnken response surface methodology (RSM) were prompted. The maximum PGase activity of 510.61 +/- 7.86 U/L was achieved at pH 5.0 after 48 h at 40 degrees C using 0.5% (w/v) pectin, 0.1% (w/v) yeast extract, 0.02% (w/v) MgSO47H2O, 0.02% (w/v) K2HPO4, 0.3% (w/v) glucose, and 0.583% (w/v) microalgae hydrolysate as a fermentation medium. PGase production without glucose was favored by SmF with a shake flask working volume of 100 ml (248.90 +/- 4.58 U/L) as compared to a bioreactor with a working volume of 1 L (192.99 +/- 0.84) for 48 h. Both carrot and apple juices were treated with the crude PGase (248.9 U/L) at different concentrations (0.1-0.5%), temperature (30-50 degrees C), and time (30-120 min), and the maximal clarification conditions were obtained as 0.3% (w/v) enzyme concentration at 50 degrees C for 30 min exposure time. This study revealed that microalgae-derived PGase in crude form could be effectively used for clarification of the juices.
Production of Microalgae-Derived Exo-Polygalacturonase for Fruit Juice Clarification
Kurhan, Sebnem/0000-0003-2242-0703
Keywords: Microalgae-Derived Polygalacturonase; Microalgae; Clarification; Bioreactor; Submerged Fermentation